Cholestyramine Influences Meal-Stimulated Pancreaticobiliary Function and Plasma Cholecystokinin Independent of Gastric Emptying and Food Digestion - Thimister, P. W. L.; Hopman, W. P. M.; Loualidi, A.; Rosenbusch, G.; Willems, H. L.; Trijbels, F. J. M.; Jansen, J. B. M. J. (Scand J Gastroenterol, 1997)
Background: Cholestyramine enhances gallbladder emptying and plasma cholecystokinin responses to oral ingestion of a mixed meal. It is not known whether this effect occurs independently of alterations in gastric emptying or maldigestion of nutrients. Methods: We perfused 15 g of an amino acid meal intraduodenally for 60min in seven healthy volunteers, once with and once without cholestyramine. Intraduodenal perfusion of saline with or without cholestyramine (6 g/h) was started 60 min before the amino acid meal and continued for 2 h. Results: Cholestyramine markedly enhanced the incremental plasma cholecystokinin response to the meal from 36 ±12 to 139 ± 25 pmol/1 60 min (P < 0.005), incremental amylase output from 2.4 ± 0.7 to 5.7 ± 0.7 kU/h (P < 0.05), and incremental integrated gallbladder contraction from1948 ± 235 to 2840 ± 189% 60 min (P < 0.05). Conclusion: The enhancing effect of cholestyramine on postprandial gallbladder contraction, pancreatic enzyme secretion, and plasma cholecystokinin release is not dependent on gastric emptying rates or appropriate digestion of nutrients.